ASPECTS REGARDING MULTINATIONAL LOGISTIC SUPPORT IN NATO OPERATIONS. LIMITATIONS AND CONSTRAINTS - Robert-Cristian TRIF (Bulletin of "Carol I" National Defense University, 2022)
Within the North Atlantic Treaty Organization / NATO we have in most cases operations and activities supported in a multinational environment, diverse and especially different in terms of technology and levels of training. The logistics of military actions is one of the pillars and basic factors taken into account right from the moment of their preparation, which initiates a widespread need to understand the phenomenon of multinational logistical support, both tactically and operationally, as well as issues related to legality, funding, responsibilities, limitations and constraints. We also believe that multinational logistical support must primarily reflect the interests of the state and, secondarily, the obligations of the state that generates the logistical support in accordance with the treaties, conventions and alliances to which it is a party. At the same time, we believe that the harmonization of national strategic cultures and logistics cultures is a major challenge that will find a rather difficult answer. Also, noting the current technological advancement but also the growing threats of Russia, we believe that defining on the territory of one of the NATO member states on the eastern border a large and rapid reaction logistical support capacity would be one of the solutions for ensuring the least material support of NATO's eastern countries in the event of military aggression that would invoke Article 5. Major logistical support provided by the alliance could support frontline countries to military support from other members, thus decongesting the material burden, being able to focus on the conduct of combat actions.